Kandungan Kalsium Dan Karbohidrat Bakso Daging Sapi Dengan Penambahan Jamur Tiram (Pleurotus sp) - Takarina, Handy Luksita (2013)
The purpose of this study was to determine calcium and carbohydrate contents in beef meatballs with oyster mushrooms. The research used Completely Randomized Design (CRD) with 1 factor pattern. Data was collected by performing experiment on each treatment, T0 (control treatment 100% of beef); T1 (40% of oyster mushrooms 60% of beef); T2 (50% of oyster mushrooms 50% of beef, and T3 (60% of oyster mushrooms 40% of beef). Calcium and carbohydrate contents were measured using spectrophotometer method. Calsium content of each treatments was 60 mg; 71,33 mg; 96,33 mg; 111,67 mg/ 100 g meatball for T0, T1, T2, T3 respectively. The highest calcium's content is found in T3 (111,67 mg) and the lowest calcium's content is found in T0 (60 mg). Carbohydrate content of each treatment was 2,72 g; 3,93 g; 4,02 g; 6,67 g/100 g meatball for T0, T1, T2, T3 respectively. The highest carbohydrate content is found in T3 (6,67) g and the lowest carbohydrate content is found in T0 (2,72 g).